The effectiveness of debt rule on fiscal sustainability: do macroeconomic data matter? - Cahyadin, Malik; Sarmidi, Tamat; Khalid, Norlin; Siong, Hook Law (Universiti Malaysia Sarawak, 2023)
The effectiveness of the debt rule to achieve a certain level of public debt and debt sustainability targets is one of the fiscal sustainability discussed in the literature. The current study attempts to estimate the impact of the debt rule on fiscal sustainability indicators for 77 countries during 1985 - 2018. There are two existing indicators are widely utilized cover primary gap and recursive algorithm. To deal with the potential of a random walk of the variables, the two-step system generalized method of moment (GMM) estimator is employed. Specifically, the current study constructs a new fiscal sustainability indicator by incorporating financial technology (FinTech) using principal component analysis (PCA) for 67 countries in 2014 and 2017. The new indicator is the main contribution on the existing literature of fiscal sustainability. The findings reveal that the debt rule has a positive and significant impact on the primary gap, either in the short- or medium-term, implying that the debt rule is effective in encouraging fiscal sustainability. Conversely, it has a negative and significant impact on the recursive algorithm. Similarly, this rule significantly contributes on the new indicator by incorporating FinTech. Therefore, policymakers are challenged to conduct this rule as a key fiscal rule in fiscal sustainability policy. The policymakers should also take more attention to increase the level of FinTech to guarantee fiscally sustainable level.